Effect of the Aquatic Plant Hydrella vorticellata as a Fertilizer on Seed Germination and some Chemical and Cytogenetics Parameters in the cell of Hordeum vulgare and Vicia faba (Baghdad Science Journal, 2016)
The present study is concerned with studying the effect of aquatic plant Hydrella vorticellata with the concentration of 10 and 20 gm/2 K gm soil on percentage and growth rate of germinating seeds of Hordeum vulgare and Vicia faba. More overs, the quantitative amount of NPK in both tested plants and Hydrella vorticellata, are estimated as an organic fertilizer. It has also been find the total number of root cells, the number of dividing cells, and stages of mitosis.The study reveales, that there are no significant differences between the concentration of hydrella used in germination percentage, growth rate, wet and dry weight. While there are differences in the plants containing NPK.The number of cells dividing stages and number of dividing cells are increased significantly.